Pengembangan Sistem Informasi Manajemen Persuratan di Badan Informasi Geospasial - Irwansyah, Irwansyah (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2021)
This study aims to produce a website-based correspondence management information system that creates a smooth, effective and efficient written communication in accordance with official scripts in the Geospatial Information Agency (BIG). The research method used in this research is the Observation and Literature Study method with the Waterfall development model, the system modeling tools with the Unified Modeling Language (UML), and the programming language used is PHP & MYSQL as a database. The Correspondence Management Information System built is a system that features the compose of official scripts / letters and the drafting process can be carried out not only in the office, the realization of integration in making official manuscripts / letters in terms of format, procedure, authority, validity and control, and can suppress the use of paper so as to save costs in the process of drafting manuscripts / letters that support the government program in bureaucratic reform. This correspondence application can be redeveloped so that you can add an electronic signature or digital signature with a QR Code or the like.